Pakistan at 100 : Structural Transformation - Sharma, Siddharth (World Bank, Washington, DC, 2019)
This policy note was prepared in parallel to the report Pakistan at 100 - Shaping the Future. The report Pakistan at 100 discusses options to accelerate and sustain growth in Pakistan so that the country becomes an upper middle-income country when it turns hundred years old in 2047. This policy note discusses Pakistan’s slow transformation and the need to reallocate resources to the most productive uses.